Integration of Artificial Intelligence in Visual Branding of Tanah Liek Batik: A Visual Communication Design Perspective - Muhammad Syukri Erwin; Lailatul Himni (fakultas Desain Komunikasi Visual, 2025)
Tanah Liek batik, as one of Minangkabau's cultural heritages, faces serious challenges in the era of globalization due to the dominance of modern visual products that are more adaptable to the digital market. This research begins with the problem of the weakness of visual communication strategies that are able to represent cultural identity in a contextual and relevant manner for today's audience. To address this issue, the research developed an Artificial Intelligence (AI)-based visual marketing strategy oriented towards strengthening cultural identity while increasing product competitiveness. A qualitative-descriptive approach was used through a series of stages including the creation of an AI-based visual design prototype, which was then validated through brainstorming with the store manager as the research partner. The results of the study show that the integration of cultural values ​​with AI technology can produce visual branding that is not only aesthetically appealing but also strengthens the cultural narrative inherent in Tanah Liek batik. The AI-based design prototype proved adaptive to digital trends, while the brainstorming provided practical validation regarding the design's relevance to market needs. In conclusion, an AI-based visual strategy can be an innovative model for cultural preservation and marketing of local products in the digital era.